A case of allergic bronchopulmonary aspergillosis successfully treated with mepolizumab - Terashima, Takeshi; Shinozaki, Taro; Iwami, Eri; Nakajima, Takahiro; Matsuzaki, Tatsu (BMC pulmonary medicine, 2018)
Allergic bronchopulmonary aspergillosis (ABPA) is an allergic pulmonary disease comprising a complex hypersensitivity reaction to Aspergillus fumigatus. Clinical features of ABPA are wheezing, mucoid impaction, and pulmonary infiltrates. Oral corticosteroids and anti-fungal agents are standard therapy for ABPA, but long-term use of systemic corticosteroids often causes serious side effects. A 64-year-old woman was diagnosed with ABPA based on a history of bronchial asthma (from 40 years of age), elevated total IgE, the presence of serum precipitating antibodies and elevated specific IgE antibody to A. fumigatus, and pulmonary infiltration. Bronchoscopy showed eosinophilic mucoid impaction. Systemic corticosteroid therapy was initiated, and her symptoms disappeared. Peripheral eosinophilia and pulmonary infiltration recurred five months after cessation of corticosteroid treatment. Systemic corticosteroids were re-initiated and itraconazole was added as an anti-fungal agent. The patient was free of corticosteroids, aside from treatment with a short course of systemic corticosteroids for asthma exacerbation, and clinically stable with itraconazole and asthma treatments for 3 years. In 2017, she experienced significant deterioration. Laboratory examination revealed marked eosinophilia (3017/μL) and a chest computed tomography (CT) scan demonstrated pulmonary infiltration in the left upper lobe and mucoid impaction in both lower lobes. The patient was treated with high-dose inhaled corticosteroid/long-acting beta-agonist, a long-acting muscarinic antagonist, a leukotriene receptor antagonist, and theophylline; spirometry revealed a forced expiratory volume in 1 s (FEV ) of 1.01 L. An uncontrolled asthma state was indicated by an Asthma Control Test (ACT) score of 18. Mepolizumab, 100 mg every 4 weeks, was initiated for the treatment of severe bronchial asthma with ABPA exacerbation. Bronchial asthma symptoms dramatically improved, and ACT score increased to 24, by 4 weeks after mepolizumab treatment. Peripheral eosinophil count decreased to 174/μL. Spirometry revealed improvement of lung function (FEV : 1.28 L). A chest CT scan demonstrated the disappearance of pulmonary infiltration and mucoid impaction. To our knowledge, this is the first case of ABPA to be treated with mepolizumab. Dramatic improvements were observed in symptoms, lung function, peripheral eosinophil counts, and chest images. Mepolizumab could serve as an alternative treatment with the potential to provide a systemic corticosteroid-sparing effect.